Inventory of Historical Sites in North Padang Lawas District - Tanjung, Agus Salim; Ali, M Nasihudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This article examines the inventory of historical sites in North Padang Lawas Regency, which have significant Hindu-Buddhist cultural heritage. The urgency of this research lies in efforts to preserve historical sites that are threatened with extinction due to natural factors, human actions, and lack of attention from the government and local communities. The problem faced is how to document and preserve these sites so that they can be a source of information and further research. The methodology used in this research is a qualitative approach with descriptive methods. Data collection techniques include direct observation, in-depth interviews, and documentation studies. Data sources came from historical sites in North Padang Lawas Regency, including the Bahal temple complex and ancient Batak tombs. Data analysis techniques involved the steps of data organisation, data reduction, data presentation, and conclusion drawing. Data validity testing was conducted through triangulation of data sources and methods to ensure the accuracy and validity of the findings. The results showed that North Padang Lawas Regency has a number of important historical sites, such as the Bahal temple which was built between the 11th and 14th centuries AD. Many of these sites are endangered and require serious preservation efforts. The research provides recommendations for increased government and community attention in preserving this cultural heritage, as well as the importance of more comprehensive documentation for future research and educational purposes.